Climbing the Resilient Path: Stages of Resilience for Children in Conflict with the Law - Nailatin Fauziyah; Maulana Galileo Budi Cendekia (International Conference on Sustainable Health Promotion, 2025)
To examine in depth how ABH navigate difficult situations during the legal process for their cases, the author conducted in-depth interviews with ABH in their respective locations to understand the stages of resilience and insecurity they experienced during the legal process. Four children under 18 years old were charged with theft and assault. The case was resolved using a restorative justice approach through police diversion. Verbal statements from the children were recorded and organized into themes, then categories were created to form the basis for developing a conceptual framework for the stages of resilience. Four stages were found in the development of ABH resilience: stress, deteriorating, adapting and recovering, and strengthening. The stress stage occurs during the process of being arrested for a crime. ABH at this stage feels very stressed because the legal impacts that occur are never previously thought of. The deteriorating stage is where ABH due to the stressful situation experiences a psychological decline, does not know what to do, and feels helpless. The adapting and recovering stage is the stage where ABH begins to develop adaptive behaviors to the existing situation and recover from the psychological conditions experienced previously. In the strengthening stage, ABH has begun to demonstrate success in adapting to the situation and developing positive behaviors. The success of this stage is influenced by the strength of protective factors during the legal process.